ALTERNATIF PEMILIHAN STRATEGI PEMASARAN OLAHAN IKAN BUNTAL (Lagocephalus spadiceus) BERDASARKAN ANALISIS SWOT PADA AGROINDUSTRI JAYA UTAMA KOTA PROBOLINGGO - Ika Kurnia Julistia Ningsih; Triana Dewi Hapsari (UNEJ e-Proceeding, 2018)
Lagocephalus spadiceus is one of the marine fisheries that has not been widely explored and utilized. Agroindustri Jaya Utama is one of the agro-industries in the City of Probolinggo that is able to utilize and develop Lagocephalus spadiceus through the processing process. Pufferfish by the community are known as poisonous fish and are not safe for consumption, so it becomes a challenge for Agroindustri Jaya Utama to market its products. The selection of alternative marketing strategies needs to be done appropriately through an internal and external environment analysis faced by the company. Based on this, the purpose of this study is to find out the alternative marketing strategies for Pufferfish processed products that can be carried out by Jaya Utama Agroindustry in Mayangan District, Probolinggo City. The sampling method used in the study was purposive sampling method. Data retrieval method uses structured interview method and documentation. The data analysis method used is the SWOT analysis. The results of this study are alternative strategies that can be used by Agroindustri Jaya Utama covering 1) improving the ability of the marketing workforce, 2) improving product quality so that products can compete with competing products, 3) opening outlets in strategic locations, 4) establishing partnerships with suppliers , 5) cooperate with potential distributors, 6) carry out promotions on an ongoing basis, 7) create new designs and flavors.